Future social impacts arising from the aging of the Portuguese population (International Journal of Geoscience, Engineering and Technology, 2022)
In recent years, the population of Portugal has experienced significant variations. It was found that the total population of Portugal has been decreasing since 2009, when it had 10.64 million inhabitants, and in the year 2021, the population was estimated at 10.34 million people and suffered a population reduction of around 300 thousand inhabitants when compared to 2009. In 1981, the country had 44.9 elderly people for every 100 young people, however in 2021, there are 182.1 elderly people for every 100 young people in a period of just 40 years. The Portuguese population continues on a downward trajectory, which will have a short and medium impact on public health and pension policies. Measures will be needed to alter and change public policies in health and education, especially in terms of social security. Measures must be taken to encourage couples to increase the number of children, and incentives must be applied to ensure a gradual increase in the number of children in Portugal.